The human brain (Chatsworth, CA : AIMS Multimedia, 1997)
This cd-rom program contains complete linear video, interactive quiz with video reinforcement, bulletin board, glossary, test with record keeping and teacher management system.
This cd-rom is available at Makmal Digital,PPKL
System requirements : Macintosh ; drag folder to your hard drive then double click on the program icon.
System requirements :Windows ; run' install.exe' from cd-rom then double click on the program icon..